Excision of Oral Verrucous Hyperplasia With Long Term Follow Up: A Case Report - Nakka Abhishek,; Aathira Velu,; Vikas Kumar Kirar,; Meghna Mehta,; Bhakti Rajput, (Public Health, 2026)
Oral verrucous hyperplasia (OVH) is a benign but a potentially premalignant exophytic epithelial lesion, often it is considered as a precursor to verrucous carcinoma. Clinically, it presents as a white, warty, or cauliflower-like growth, commonly seen on the buccal mucosa, gingiva, or alveolar ridge. It is frequently associated with chronic tobacco or betel quid use. Accurate diagnosis and complete excision are crucial. Both clinically and histologically Oral verrucous hyperplasia may mimic verrucous carcinoma